A nationwide study exploring the factors associated with psychological resilience during the COVID-19 pandemic in Singapore - Gunasekaran, Savita; Tay, Eng Hong; Shafie, Saleha; Shahwan, Shazana; Wang, Peizhi; Zhang, YunJue; Satghare, Pratika; Tan, Sing Chik; Ni, Michael Y.; Lun, Phyllis; Chong, Siow Ann; Subramaniam, Mythily (Frontiers in Public Health, 2025)
BackgroundThe COVID-19 pandemic is a global adverse event that affected many individuals’ well-being. Resilience is an essential component that allows one to cope during stressful events such as the pandemic. Not many studies have longitudinally explored changes in resilience across time during the pandemic in the Southeast Asia region. The current article investigates resilience and the sociodemographic and psychological factors associated with resilience across two waves of survey of a Singapore adult population.MethodsThe study was conducted across two timepoints from May 2020 to June 2021 (T1) and October 2021 to September 2022 (T2). 1129 participants partook during T1 (response rate = 54.8%) and 858 participants partook during T2 (response rate = 76.0%). The questionnaire included sociodemographic information and measures such as the Brief Resilience Scale, Patient Health Questionnaire-9, Generalized Anxiety Disorder Scale-7, the stress component of the Depression, Anxiety and Stress Scale, and four COVID-19-related stressors. Generalized estimating equations (GEE) were utilized to investigate the relationships adjusting for timepoints.ResultsMost participants had normal levels of resilience (M = 3.61, SD = 0.62), and resilience scores did not differ much over time (p = 0.852). Males, younger adults, university-educated, employed individuals, and individuals living in private housing had higher levels of resilience. Higher levels of anxiety symptoms, depressive symptoms, stress, and one specific COVID-19-related stressor (i.e., employment concerns) were associated with lower levels of resilience. Individuals who reported having moderate to severe depression and anxiety symptoms were more likely to have low resilience.DiscussionThe findings suggest that resilience levels remained within the normal range and unchanged over time, reflective of the population’s ability to cope with the pandemic. However, there is still a need for more targeted interventions for individuals who are more vulnerable to lower resilience. Continued research is also needed to understand the long-term psychological effects of the pandemic.